Study about Trimorphic Extreme Clubfoot Deformities and their Management by Triple Surgical Skin Expanders (DOLAR, DOLARZ and DOLARZ-E) - Rattan L. Mittal; Suruchi Chopra (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
The primary aim of this study has been to treat, hitherto neglected extreme deformities, achieving a longer/ flexible foot without fusion with high acceptability. Congenital foot deformities are frequently present at birth, persist in children, adolescents, and adults, and are either left untreated or under-corrected by conservative and/or surgical methods. These deformities are reported under different names that have no effective treatment; most of them advocate arthrodesis, which is unacceptable. The author researched this grey area for more than 50 years and successfully innovated improved surgical corrections, more acceptable to patients. This research is in three stages/ generations, with distinct timeline and completely evidence based. All were given a generic name: Extreme deformities, with 3 hierarchic grades, each 3D (trimorphic), because of their common aim, i.e. a good correction. The author started with anatomical dissections in 15 clubfeet collection in the anatomy museum of GOMCO Patiala (zero cost), consistently reinforced with solid clinical background. Heterogeneous skin contractures: congenital (primary) and secondary with scars, were discovered as the causes with cramped deeper tissues and author evolved, evidence based, 3D enlargement of skin chamber by triple expanding incisions: DOrso-LAteral Rotation skin flap (DOLAR- acronym) for grade I, DOLAR + Z-plasty (DOLARZ) for grade II and DOLAR + Z + VY-plasty (DOLARZ-E) for grade III, E means Extended. Patient satisfaction level (excellent, good, fair & poor) had been considered for grading results, rather than scoring systems because each clubfoot is different with countless variables. The author operated 1080 feet during the last 40 years with long term follow up, six months to 30 years, with an average of 12½ years. The results obtained were: excellent/good (96%) and fair/poor in (4% including superficial skin necrosis only in 3%, evidence based). Triple surgical skin expansion consistently resulted in longer, flexible, joints sparing, good shaped, better functioning foot; even in adults. Assessment criteria have been based on patient satisfaction level, because each clubfoot is different^ with myriad vari-ables depending upon: deformity components, age, weight bearing, syndromic/ others, previous surgeries, complications, radiological osteo-articular differences.